ANALISIS MISKONSEPSI LITERASI SAINS MENGGUNAKAN THREE TIER MULTIPLE CHOICE TEST MATERI CAHAYA - Sri Wahyuningsih; Ani Rusilowati; Nathan Hindarto (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2018)
Recently mastery of scientific literacy for students has become the focus of education. The level of scientific literacy skills of students in Indonesia is low, which is influenced by misconceptions. So far, study on the development of diagnostic tests that uncover the misconception of scientific literacy is still limited, whereas it is much needed to improve the learning system in Indonesia. The result of observation and interview of scientific lesson in SMP Negeri 05 Semarang shows that students having difficulties in studying light materials and evaluation tools used by teachers are not continued to reveal misconception of scienctific literacy. The aims of this study to develop three tier multiple choice (3TMC) test with the scientific literacy aspect and to find the misconception of students' light scientific literacy. The research sample is class VIIIE and VIIIF with mix method of sequential explanatory strategy. The result of 3TMC test instrument with scientific literacy aspect which is developed which is 30 item where 25 items fulfill criteria with valid result, reliable, sufficient distinguishing, medium difficulty level while 5 grains are not used. The results of the interpretation indicate that the average learners have misconception of scientific literacy aspects of knowledge (A), science investigation competence (B), science as a way of thinking (C) and application of science to technology, society and environment. In-depth interviews were conducted on 7 students who experienced the highest misconception of scientific literacy. The result they experience misconceptions of scientific literacy indicators of light properties, viewing processes, eye defects and optical devices.